Research on the Practice of Railway Transportation Supply Chain Management for GAC Trumpchi Automobiles to Urumqi - Qiwei Liu; Minguo Ma (中国科学与技术学报, 2025)
This paper takes the transportation business of GAC Trumpchi automobiles from Guangzhou to Urumqi Sanping Station by railway and then distributed to Kashgar, Yili and other regions as the research object. Focusing on the core work links such as vehicle identification number (VIN) management, system information entry, real-time location update and terminal vehicle delivery verification, it analyzes the operation process and management characteristics of the automobile transportation supply chain, points out the advantages and potential problems in the current process, and puts forward optimization suggestions. The research aims to provide practical reference for the supply chain management of long-distance automobile railway transportation and regional distribution, and help improve the efficiency and service quality of automobile logistics and transportation.This paper takes the transportation business of GAC Trumpchi automobiles from Guangzhou to Urumqi Sanping Station by railway and then distributed to Kashgar, Yili and other regions as the research object. Focusing on the core work links such as vehicle identification number (VIN) management, system information entry, real-time location update and terminal vehicle delivery verification, it analyzes the operation process and management characteristics of the automobile transportation supply chain, points out the advantages and potential problems in the current process, and puts forward optimization suggestions. The research aims to provide practical reference for the supply chain management of long-distance automobile railway transportation and regional distribution, and help improve the efficiency and service quality of automobile logistics and transportation.